Implementation and effectiveness of the internal credit risk rating in the banking industry: a study on Dhaka Bank Limited - Mahmud, Mostansir (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.